Different effects of a perioperative single dose of dexamethasone on wound healing in mice with or without sepsis - Chen, Yuanyang; Chen, Xiaoshan; Zhou, Quanhong (Frontiers in Surgery, 2023)
Introduction Sepsis delays wound healing owing to uncontrolled inflammation. A single perioperative dose of dexamethasone is widely used because of its anti-inflammatory effects. However, the effects of dexamethasone on wound healing in sepsis remain unclear. Methods We discuss the methods to obtain dose curves and explore the safe dosage range for wound healing in mice with or without sepsis. A saline or LPS intraperitoneal injection was applied to C57BL/6 mice. After 24 hours, the mice received a saline or DEX intraperitoneal injection and full-thickness, dorsal wounding operation. Wound healing was observed by image record, immunofluorescence and histological staining. Inflammatory cytokines and M1/M2 macrophages in wounds were determined by ELISA and immunofluorescence, respectively. Results Dose-response curves reflected the safe dosage range of DEX in mice with or without sepsis, from 0.121 to 2.03 mg/kg and from 0 to 0.633 mg/kg, respectively. we found that a single dose of dexamethasone (1 mg/kg, i.p.) promoted wound healing in septic mice, but delayed wound healing in normal mice. In normal mice, dexamethasone delays inflammation, resulting in an insufficient number of macrophages during the healing process. In septic mice, dexamethasone alleviated excessive inflammation and maintained the balance of M1/M2 macrophages in the early and late healing process. Discussion In summary, the safe dosage range of dexamethasone in septic mice is wider than that in normal mice. A single dose of dexamethasone (1 mg/kg) increased wound healing in septic mice, but delayed it in normal mice. Our findings provide helpful suggestions for the rational use of dexamethasone.